L PENGUATAN KOMPETENSI GURU DALAM IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA - Leny Noviani; Feri Setyowibowo; Budi Wahyono (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2023)
In the 2022–2023 academic year, the government provides options related to the implementation of the Kurikulum Merdeka. In the 2022–2023 academic year, more than 140 thousand schools have chosen the options Mandiri Berubah, meaning that schools are implementing an independent curriculum using tools provided by the government. Schools that choose the the options Mandiri Berubah, independently conduct training, or study independently about the Kurikulum Merdeka. SMA Negeri 2 Surakarta is a school that chooses the the options Mandiri Berubah. The problem that is the partner's priority is how to design, implement, and evaluate the implementation of the Proyek Penguatan Profil Pelajar Pancasila (P5). The solution to overcome this is training on the implementation of P5. This method has a participatory approach. The training activities were attended by 44 teachers. The implementation phase includes six hours of face-to-face training, followed by independent assignments and assistance in preparing project modules. Participants' understanding of the material can be seen from the comparison of pre-test and post-test scores, which showed an increase from an average of 67 to 80. Based on feedback from participants, it was shown that participants rated this training program as very good in terms of clarity of activity objectives, relevance of activities to the needs of participants, the systematic presentation of the material, the added value of the material presented, and the achievement of activity objectives. As seen from the adequacy of time allocation in the good category.